2019
DOI: 10.1136/bmjopen-2019-029742
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and reporting standards of psychological interventions for improving short-term and long-term pain outcomes after total knee replacement: a systematic review

Abstract: ObjectivesTo assess the effectiveness and reporting standards of psychological interventions for improving outcomes after total knee replacement (TKR).DesignMedline, Embase, and PsycINFO were searched from inception to up to 9 May 2019 with no language restrictions applied. Randomised controlled trials (RCTs) assessing the effectiveness of psychological interventions for short-term and long-term postoperative pain after TKR were included. Screening, data extraction, and assessment of methodological quality wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 71 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…Regarding orthopaedic research, Giordano et al [ 21 ] proposed that the application of JRT in postoperative multimodal analgesia in orthopaedic trauma patients reduced average hospital stay length. Whale et al [ 22 ] also found that the application of JRT after total knee arthroplasty was helpful for pain management in a multicenter clinical trial. However, there is no relevant research on the application of JRT in patients with malignant bone and soft-tissue tumors in China.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding orthopaedic research, Giordano et al [ 21 ] proposed that the application of JRT in postoperative multimodal analgesia in orthopaedic trauma patients reduced average hospital stay length. Whale et al [ 22 ] also found that the application of JRT after total knee arthroplasty was helpful for pain management in a multicenter clinical trial. However, there is no relevant research on the application of JRT in patients with malignant bone and soft-tissue tumors in China.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, previous systematic reviews regarding psychological interventions in improving outcomes following TKR included musical therapy, hypnosis, guided imagery, and other different types of psychological interventions [33]. Due to its high heterogeneity, attaining a firm conclusion about the effectiveness of musical interventions in those treated with TKR is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous OA studies have illuminated the importance of social relationships in this population; for example, partner-supported interventions demonstrate enhanced benefits in OA patients [ 134 136 ]. Other non-pharmacologic treatments that enhance protective factors and reduce psychosocial risk factors (e.g., anxiety, catastrophizing) have shown promise in improving joint replacement outcomes as well [ 137 ].…”
Section: Discussionmentioning
confidence: 99%